Microbiological Assessment of Titanium Plates Coated with PLGA, Chitosan, and/or Meropenem: An In Vitro Study - Mohammad Al-Qubaisey; Rita Khounganian; Abdulhakim Al-Badah (MDPI AG, 2022)
This investigation was conducted to evaluate the efficacy of coated titanium plates against gram-positive Staphylococcus aureus (SA) and gram-negative Pseudomonas aeruginosa (PA) using various methods. The Colony-forming unit "CFU" was higher in chitosan (CH) in relation to PA than in poly lactic-co-glycolic acid (PLGA) in relation to SA, followed by meropenem-chitosan "MC" coated plates in relation to PA and SA. A significant difference in the zone of inhibition (ZOI) of SA was determined in MP, MC, and meropenem (MEM). PA was significantly inhibited by MP, MEM, then MC, and the largest ZOI among SA and PA groups were MP coating. Using an MTT assay, MP had the lowest bacterial viability in the SA group, followed by MC and MEM, with no statistically significant difference between the PLGA or CH alone nor the polymers augmented with MEM. Using confocal microscopy, MP-coated plates were seen to have the highest bacterial inhibition, followed by MC, MEM, PLGA, and CH. In the PA group, MP had the highest bacterial inhibition, followed by MEM, MC, CH, and PLGA. The uncoated group presented the lowest inhibition in relation to both SA and PA. Conclusively, coating titanium plates with PLGA or CH with MEM appeared to enhance the antibacterial efficacy as opposed to MEM without polymers through bacterial adhesion inhibition, hindering biofilm formation and preventing bacterial proliferation.